Hubungan Diameter Pasak, Lubang Sambungan Dan Ketebalan Plat Terhadap Distribusi Tegangan Sisa - Wahjudi, Ari; Purnowidodo, Anindito; Pambudi, Wijil (Rekayasa Mesin, 2011)
The discontinuities on the structures or members are often to be encountered such as, rivet and bolt holes as well as notches. These discontinuities are agents for stress raiser and itcan initiate cracks in the vicinity of holes or in the notch roots. It is well known that most of the fatigue failure is caused by cracks growth initiated from the discontinuities. To reduce possibilitythe initiation of crack in those stress raisers, the compressive residual stress, in general, is imposed to the region in which the stress concentrates. In the present study, using expansionhole technique carried out by aid of computer simulation, the effect of mandrel diameter and thickness of the blank to the residual stress in the vicinity of the hole is investigated. The result shows that the magnitude of the residual stress in the vicinity of the hole varies depending onthe magnitude of the expansion and the thickness of blank. In addition, in the certain distancefrom the hole, the tensile residual stress develops, hence, it may endanger a component because it causes the crack growth rate increase, as consequent, the life time of a componentis shorter.Keyword: mandrell diameter, hole diameter, thickness, residual stress distribution